Hypochondriasis: A Literature Review - Ahmad Syaukat (Scientia Psychiatrica, 2021)
Hypochondriasis is one of six somatoform disorders categorized in the DSM-IV. Hypochondriasis is distinguished from other somatic delusional disorders because this disorder is associated with the experience of physical symptoms experienced by the sufferer, whereas other somatoform disorders do not show physical symptoms in themselves. Symptoms that arise may be an exaggerated statement of physical symptoms, which will actually exacerbate physical symptoms caused by the belief that the patient is sick and in a worse condition than the actual situation. Treatment of hypochondriasis includes recording symptoms, psychosocial review, and psychotherapy. Good prognosis is associated with high socioeconomic status, sudden onset, absence of personality disorders and absence of concomitant non-psychiatric medical conditions.